MEASURING MARKET CONCENTRATION OF CONSTRUCTION INDUSTRY. VLORA REGION EVIDENCE - Pulaj (Brakaj), Enida; Kume, Vasilika (European Scientific Journal, ESJ, 2013)
The concentration ratio indicates the concentration of production management in a particular industry and is and important index to reflect industry and market structures. The research shows that the concentration of construction industry market definitely has developed. The study was conducted in the construction industry during a ten year period in Vlora region. The annual sales data during the years 2003-2013, were collected to compute comparable measures of market concentration. As, the market concentration may used as a measure of competition, theorized to be positively related to the rate of profit in the industry, it is evident that companies try to choose the appropriate strategies which fit more with the industrial organization. This paper applied concentration ratio (CR4) method, HHI and Gini Coefficient to analyze the absolute concentration ratio and relative concentration ratio for yconstruction industry market with 2003 to 2012 statistical data. The principal aim of this paper is to make an evaluation and to analyze the issues concerning the market concentration of construction industry in Vlora region. The specific objectives of the paper are: (1) to determine the role and challenges of construction industry firms in Albania and (2) to measure the level of firm concentration in the construction industry in Vlora Region. The study therefore attempted to test the hypothesis that the construction industry is not concentrated. The results of this study would assist the menagers to design better competitive strategies they have to compete. According the purpose of this work there are following the description and comparative methods.